Development of E-LKPD Wizer: A Solution to Improve Problem Solving Skills and Ecological Attitude in Junior High School Students - Siti Fathonah Septianingsih; Nurasyah Dewi Napitupulu; Mery Napitupulu; Ratman; I Nengah Kundera (Jurnal Penelitian Pendidikan IPA, 2024)
The objective of this study was to develop and assess the impact of Wizer E-LKPD on the problem-solving skills and ecological attitudes of 28 VIIC class students at SMP Negeri 1 Wita Ponda. The study employed the ADDIE model as its research framework and utilized a one-group pretest-posttest design with purposive sampling. The research instruments included validation sheets, response questionnaires completed by teachers and students, tests of problem-solving abilities, and an ecological attitude questionnaire. The findings indicated that Wizer E-LKPD was highly valid, with an average rating of 94.12%. The results demonstrated that the Wizer E-LKPD effectively enhanced problem-solving skills, achieving a medium effect size of 0.65, and improved ecological attitudes with a simple effect size of 0.30. Therefore, it can be concluded that the Wizer E-LKPD is a valid, practical, and effective tool for improving students' problem-solving abilities and fostering ecological attitudes in science learning at SMP Negeri 1 Wita Ponda.